Tourism and Sustainable Development in Russia: Current Challenges and Constraints - Afanasieva, Alexandra; Filatova, Maria; Nikolskaya, Elena (Anais Brasileiros de Estudos Turísticos, 2022)
The sustainable tourism development has become a prerequisite for the industry functioning. Sustainable tourism is now seen as a logical response to a growing tourist flow, and as a result, to an excessive burden on the natural and historical and cultural environment of destinations. In Russia, sustainable development is a complex and painful issue. Ambiguity of responsibility areas and the lack of thoughtful and well-established regulatory mechanisms make the interaction between business and government in sustainable territory development a particularly difficult issue in Russia. That is why the purpose of this study is to reveal how the representatives of the tourism business understand the need for sustainable tourism development in Russia. The survey of business representatives conducted in the article made it possible to identify problems in understanding the essence of sustainable tourism development, and to identify the sustainable tourism trends, which in many ways demonstrate the growing need for the transition of the tourism industry in Russia to the principles of sustainable development. One of the important problems of sustainable tourism development in Russia is the professional personnel training. For this purpose, the authors have developed a combined model of educational activities in the "challenges-needs" system for the sustainable development of hospitality industry. It is intended for stakeholders of the tourism market and is aimed at raising awareness and building sustainable interaction.